Contracts, Hold-Up, and Exports: Textiles and Opium in Colonial India - Kranton, Rachel; Swamy, Anand V (American Economic Review, 2008)
Trade and export, it is argued, spur economic growth. This paper studies the microeconomics of exporting. We build a heuristic model of transactions between exporters and producers and relate it to East India Company (EIC) operations in colonial Bengal. Our model and the historical record stress two difficulties: the exporter and its agents might not uphold payment agreements, and producers might not honor sales contracts. The model shows when procurement succeeds or fails, highlighting the tension between these two hold-up problems. We analyze several cases, including the EIC's cotton textile venture, the famous Opium Monopoly, and present-day contract farming. (JEL D86, F14, N55, N75)